IoT Technological Development: Prospect And Implication For Cyberstability - Anawar, Syarulnaziah; Zakaria, Nurul Azma; Mas'ud, Mohd Zaki; Muslim, Zulkiflee; Harum, Norharyati; Ahmad, Rabiah (The Science And Information, 2019)
Failure to address the risk poses by future technological development could cause devastating damage to public trust in the technologies. Therefore, ascendant technologies such as artificial intelligence are the key components to provide solutions for new cybersecurity threats and strengthen the capabilities of the future technological developments. In effect, ability of the technologies to prevent and withstand a cyber-attack could become the new deterrence. This paper will provide gaps to guide the government, industry, and the research community in pursuing Internet of Things (IoT) technological development that may be in need of improvement. The contribution of this paper is as follows: First, a roadmap that outline security requirements and concerns of future technology and the significant of IoT technology in addressing the concerns. Second, an assessment that illustrates the expected and unexpected impact of future technology adoption and its significant geopolitical implication on potential impacted areas such as regulatory, legal, political, military, and intelligence.